Alternating School-Work Pathways in Italy. Some Remarks on the "Competence Society" - Gremigni, Elena (PARTECIPAZIONE E CONFLITTO, 2019)
Since the mid-nineties, the European Union and UNESCO have promoted a new form of didactics aimed at developing competences. These "key competences", subsequently identified by the Council and the European Parliament, are considered as fundamental for Europe’s response to globalisation. Their close link with a neoliberal perspective of the working world - as can also be deduced from the non-random choice of the term "competence" - is evident. In particular, the competence related to the sense of initiative and entrepreneurship has assumed a strategic role within the "Lifelong Learning Programme" and the "Europe 2020" programme, fostering the spread of a new labour market model no longer based on the prevailing paid employment. Recent Italian legislation on educational institutions, and Law 107/2015 in particular, have acknowledged the European Union guidelines regarding promotion of the key competences, and more specifically of alternating school-work pathways. Although it is too early to make an overall evaluation of the effects these laws have produced, the actions promoted so far do not seem to overcome the existing inequality in Italy’s educational and employment opportunities. Furthermore, the objective of promoting competences that can be directly used on the labour market, to the detriment of broader cultural preparation deemed useless for this purpose, risks impoverishing the education of the most disadvantaged, those people who have the fewest chances of acquiring knowledge and critical thinking outside the school context. The transformations taking place in the educational field appear to proclaim the advent of a "Competence Society", the last metamorphosis of an epiphenomenon with its roots in the globalised capitalist system which is leaving social reproduction mechanisms unchanged.